Face-to-face, online, or hybrid learning in post COVID-19 recovery? Scrutinizing Nigerian students’ Preferences - Haruna Abubakar Haruna; Musa Yusuf Kabara; Alexis Enriquez (Journal of Educational Management and Instruction (JEMIN), 2022)
The shifting from face-to-face interaction in a formal classroom to digital learning outside the classroom in the recent education system has made a great change in our learning habit. As the online learning mode has become more prevalent in around the world including Nigeria due to the COVID-19 pandemic, it is particularly crucial to re-examine students’ opinions and preferences about the teaching modes. Now, a crucial question that may exist is will schools and universities keep at online learning in post COVID-19 pandemic recovery? In responding to the question, the present study scrutinizes Nigerian university students’ standpoints either to prefer online or face-to-face learning activities at the time after the global pandemic recovers. A survey design is adopted by using an online questionnaire distributed to 153 students of several departments at a university in Nigeria. The results depict that 51% of the students are in favor of studying in an online learning mode. However, it is further found that only 19% of the students prefer to have a full online learning activity after the pandemic ends. Moreover, this study reveals that the majority of the students (69%) are supporting hybrid learning system which is the combination between online and offline learning activities. The rest (12%) agree with face-to-face learning activities in classrooms. These results contribute to offering fruitful insights and policy recommendation for Nigerian Ministry of Education to design specific rules and guidelines in which schools and universities are desired to offer blended learning activities for students in post pandemic recovery.